Concentric and Eccentric Force Changes with Elastic Band and Isotonic Heavy Resistance Training: A Randomized Controlled Trial - Eric Folkins; Sidharth Sahni; John Ryan; Stacey Wooden; Gina Bushby; Christian Radzinski (International Journal of Sports Physical Therapy)
# Background